2022
DOI: 10.1101/2022.02.08.22270649
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Innovative Randomized Phase 1 Study and Dosing Regimen Selection to Accelerate and Inform Pivotal COVID-19 Trial of Nirmatrelvir

Abstract: Background: COVID-19 is a continued leading cause of hospitalization and death. Safe and efficacious COVID-19 antivirals are needed urgently. Nirmatrelvir (PF-07321332), the first orally bioavailable, SARS-CoV-2 Mpro inhibitor against the coronaviridae family, has demonstrated potent preclinical antiviral activity and benign safety profile. Methods: We report safety, tolerability, and pharmacokinetic data of nirmatrelvir with and without ritonavir as a pharmacokinetic enhancer, from an accelerated randomized,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
(38 reference statements)
0
9
0
Order By: Relevance
“…hydroxychloroquine, lopinavir, ivermectin (1-7)) or in various stages of development for other indications (e.g. remdesivir, molnupiravir, nirmatrelvir (8)(9)(10)(11)(12)). The speed at which drugs can be brought forward under the urgency of a pandemic is a significant advantage.…”
Section: Introductionmentioning
confidence: 99%
“…hydroxychloroquine, lopinavir, ivermectin (1-7)) or in various stages of development for other indications (e.g. remdesivir, molnupiravir, nirmatrelvir (8)(9)(10)(11)(12)). The speed at which drugs can be brought forward under the urgency of a pandemic is a significant advantage.…”
Section: Introductionmentioning
confidence: 99%
“…Among extraction modes, the protein precipitation method was prioritized for pretreatment due to its simple operation procedure and high plasma concentration of nirmatrelvir and ritonavir (R. S. P. Singh et al, 2022). The method mentioned previously had unparalleled advantages in processing a large number of clinical samples (Polson et al, 2003; Soltani & Jouyban, 2014; Souverain et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…The pharmacokinetic study of Paxlovid in Western participants has been reported recently (Owen et al, 2021; Ravi Shankar P. Singh et al, 2022). However, there are currently no relevant reports on Chinese volunteers.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…In general, by day 28, no casualties were informed among patients receiving nirmatrelvir, while 10 (1.6%) in the placebo group lost their lives (Figure 5) [25,30,47,48]. In another study, high confidence was obtained in the selection of the 300 mg nirmatrelvir diet in combination with the 100 mg ritonavir as BID over a 5-day term for phase 2/3 clinical trials in patients with COVID-19 [49]. Older people are at higher risk for severe complications from COVID-19.…”
Section: Safety Of Nirmatrelvir In Patientsmentioning
confidence: 99%